2002
DOI: 10.1006/viro.2002.1541
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Termination Modulated by Nucleotides Outside the Characterized Gene End Sequence of Respiratory Syncytial Virus

Abstract: The genes of respiratory syncytial (RS) virus are transcribed sequentially by the viral RNA polymerase from a single 3'-proximal promoter. Polyadenylation and termination are directed by a sequence at the end of each gene, after which the polymerase crosses an intergenic region and reinitiates at the start sequence of the next gene. The 10 viral genes have different gene end sequences and different termination efficiencies, which allow for regulation of gene expression, since termination of each gene is requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
19
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 48 publications
5
19
0
2
Order By: Relevance
“…The spacing between the conserved UCAAU and U tract and the length of the U tract were both found to be important for efficient termination (21,44). In addition to the gene end sequence, the composition of the intergenic region was important when the U tract was only four residues (22,44). This finding was similar to results with Simian parainfluenza virus 5 (37,38).…”
supporting
confidence: 75%
See 2 more Smart Citations
“…The spacing between the conserved UCAAU and U tract and the length of the U tract were both found to be important for efficient termination (21,44). In addition to the gene end sequence, the composition of the intergenic region was important when the U tract was only four residues (22,44). This finding was similar to results with Simian parainfluenza virus 5 (37,38).…”
supporting
confidence: 75%
“…The semiconserved gene end sequences of HRSV are 13 to 14 nt in length and comprised of a semiconserved A (in 8 of the 10 gene ends) followed by the conserved pentanucleotide 3Ј-UCAAU-5Ј, an A/U-rich central region of one to four nucleotides, and a U tract of four to seven residues (8,22). Thus, an HRSV gene junction is 3Ј-.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the gradient of transcription is believed to be universal for nonsegmented negative-strand viruses (50), the levels of transcription of individual genes may not necessarily follow the gradient exactly due to the regulatory role of different elements of gene junctions, which may be different for different pairs of genes. The elements, which effect transcription, include intergenic regions and transcription termination signals, as demonstrated for respiratory syncytial virus (51,52) and recently for EBOV (53). In our study, the abundance of the eGFP mRNA was lower than that of the downstream genes at both time points.…”
Section: Resultsmentioning
confidence: 50%
“…Previous studies using dicistronic minigenomes have shown that mutations in any of these three regions can significantly affect the efficiency of transcription termination, though the central region appeared to be the least sensitive (13,22). More recently, it has been suggested that the single nucleotides preceding and following the 12-to 13-nt GE signal also affect the efficiency of termination (12).…”
mentioning
confidence: 99%